2004
DOI: 10.1097/01.tp.0000144606.84234.49
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment Potential of Human Amnion and Chorion Cells Derived from Term Placenta

Abstract: Human amnion and chorion cells from term placenta can successfully engraft neonatal swine and rats. These results may be explained by the peculiar immunologic characteristics and mesenchymal stem cell-like phenotype of these cells. These findings suggest that amnion and chorion cells may represent an advantageous source of progenitor cells with potential applications in a variety of cell therapy and transplantation procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
270
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 331 publications
(289 citation statements)
references
References 37 publications
14
270
1
4
Order By: Relevance
“…After transplantation into neonatal swine and rats, human av-MSCs were able to engraft without immunosuppression [35]. Human-and mousederived av-MSCs improved bleomycin-induced lung fibrosis in a mouse model [36].…”
Section: Discussionmentioning
confidence: 90%
“…After transplantation into neonatal swine and rats, human av-MSCs were able to engraft without immunosuppression [35]. Human-and mousederived av-MSCs improved bleomycin-induced lung fibrosis in a mouse model [36].…”
Section: Discussionmentioning
confidence: 90%
“…Experimental and clinical studies have demonstrated that AM cell transplantation promotes re-epithelialisation, decreases inflammation and fibrosis and modulates angiogenesis. The cells obtained from AM can differentiate into osteogenic, adipogenic, chondrogenic and myogenic lineages in vitro (In't Anker et al 2003;Portmann-Lanz et al 2006), which might be potential source of clinical biomaterial for engraftment (Bailo et al 2004). Samandari et al (2011) used human AM cells as healing accelerator and bone induction in dogs and indicated that AM decreased fibrin-leukocytic exudates and inflammation and observed a suitable cover for experimentally induced injuries.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that cells isolated from amniotic and chorionic membranes do not induce an allogeneic or xenogeneic immune response in mixed lymphocyte reactions and are capable of actively suppressing the proliferation of lymphocytes in vitro (15). Several studies have already reported a prolonged survival of human placenta-derived cells following xenogeneic transplantation into immunocompetent animals including rats (31,32), swine (31), and bonnet monkeys (33), with no evidence of immunological rejection.…”
Section: A B Cmentioning
confidence: 99%